The Role of the Arts in the Classroom: Does Integration of the Arts Promote Social Relationships in the Classroom? - Julia Lauss; Christoph Helm (Education Sciences)
Positive social relationships between pupils are crucial for creating a conducive learning environment. Integrating the arts into classrooms fosters these relationships by promoting creative expression and social skills such as empathy, mutual support, and teamwork. Arts-based activities encourage collaboration, enabling pupils to develop creative solutions and appreciate diverse perspectives. Despite growing interest in this interdisciplinary approach, research on its impact on pupil relationships remains limited. This longitudinal study collected data from 381 pupils across five schools at two measurement points using standardized questionnaires to assess different dimensions of social relationships. Results indicated a significant increase in helpfulness and a reduction in discrimination among pupils who participated in several weeks of arts workshops. However, cliquishness and competitive thinking also increased, while aggressiveness remained unchanged regardless of group membership. These findings demonstrate the benefits of arts integration for fostering positive pupil relationships while highlighting the complex dynamics between creative learning environments and social interactions. The results underscore the need for targeted strategies to balance cooperation and competition effectively, ensuring that arts-based approaches maximize their potential to enhance classroom social dynamics.